Outcome Difference in Neurosurgical Patients Based on Timing of Tracheostomy and Ventilator Associated Pneumonia - Shrestha, Pratyush; Lohani, Subash; Shrestha, Sunita; Devkota, Upendra P (Nepal Journal of Neuroscience, 2018)
Background and Objective: Tracheostomy in neurosurgical patients has been shown in various studies to lower the length of ICU stay and the length of hospital stay by decreasing the incidence of ventilator associated pneumonia. In this regard, we wanted to evaluate the outcome of neurosurgical ICU patients based on timing of tracheostomy and ventilator associated pneumonia. Methods: This is a retrospective single centre study performed over a period of two and a half years. Early tracheostomy was defi ned as those done three days of intubation or earlier and late as those done then after. Statistical analysis was done using SPSS. Results: There were 56 patients over the study period of which 18 patients underwent early tracheostomy and 38 patients underwent late tracheostomy. There was no statistically significant difference between the two groups with regards to the length of ICU stay, the length of hospital stay or the length of tracheostomy tube in situ. But based on tracheal aspirate culture positivity, length of tracheostomy tube in situ was signifi cantly longer in those with positive bacterial cultures. Early tracheostomy does not improve neurosurgical outcome while documented pneumonia prolongs the length of tracheostomy tube in situ. Nepal Journal of Neuroscience 15:19-22, 2018